Dielectric properties of the system Ca1-xYxTi1-xCoxO3(0.00 ≤ x ≤ 0.15) - Tewari H.S.; Parkash O.; Tare V.B.; Kumar D. (My University, 2025)
The dielectric behaviour of the compositions with x≤0.15 in the system Ca1-xYxTi1-xCoxO3 sintered and cooled in air has been studied. Space-charge polarization which arises due to the presence of chemical inhomogeneities at the micro-level contributes significantly to their dielectric constant. The composition with x=0.05 exhibits temperature and frequency-independent dielectric constant and very small dielectric loss. © 1990 Chapman and Hall Ltd.